Dampak Konten TikTok terhadap Etika Anak Kelas XI SMAN - Puput Stiyaningrum; Rina Priarni; Ida Zahara Adibah (Universitas Muhammadiyah Mataram, 2026)
Abstract: The development of digital technology, especially social media like TikTok, has caused major changes in the interaction patterns and behavior of adolescents. One of the biggest challenges is the decline in learning motivation and changes in the way of social interaction. The purpose of this study is to determine the relationship between TikTok content and the ethics of eleventh grade students. Using a quantitative approach, this study involved 43 respondents as the study sample. Data were obtained through questionnaire distribution, while data analysis used the Pearson Product Moment correlation test assisted by the SPSS 22 program. The results of the statistical analysis produced a correlation coefficient (r) of 0.645 and a significance value (sig. 2 tailed) of 0.000 < 0.05. This proves that there is a strong and relevant relationship between TikTok content and student ethics. Based on this, educational institutions are advised to incorporate digital literacy into their learning and optimize periodic guidance and counseling programs to help students filter social media content wisely.Abstrak: Perkembangan teknologi digital, terutama media sosial seperti TikTok, telah menyebabkan perubahan besar dalam pola interaksi dan perilaku remaja. Salah satu tantangan terbesar adalah menurunnya motivasi belajar dan perubahan dalam cara interaksi sosial. Tujuan dari kajian ini untuk mengetahui hubungan anatara konten TikTok dengan etika anak kelas XI. Menggunakan pendekatan kuantitatif, penelitian ini melibatkan 43 responden sebagai sampel kajian. Perolehan data dilakukan melalui distribusi angket, sedangkan analisis data menggunakan uji korelasi Pearson Product moment dibantu program SPSS 22. Hasil analisis statistik menghasilkankan nilai koefisien korelasi (r) sebesar 0,645 dan nilai signifikasi (sig. 2 tailed) sebesar 0,000 < 0,05. Hal ini membuktikan bahwa ada hubungan yang kuat dan relevan antara konten TikTok dengan etika siswa. Berdasarkan hal tersebut, institusi pendidikan disarankan memasukkan literasi digital ke dalam pembelajaran dan mengoptimalkan program bimbingan penyuluhan secara berkala guna membantu siswa menyaring konten media sosial dengan bijak.